Intraparticle diffusion effects on the photodegradation of astrazon orange G dye using TiO2 photocatalyst: Optimization via response surface methodology - Dursun, Arzu Yadigar; Murshed, Mohammed Khisro; Dursun, Gulbeyi (Elsevier, 2025)
The photodegradation of Astrazon Orange G (AOG) dye using TiO2 as a catalyst was investigated with a focus on process optimization, reaction kinetics, and internal mass transfer effects. The catalyst's crystalline structure, BET surface area, and average pore diameter were characterized. Response Surface Methodology was used to evaluate the interaction of key parameters, including dye concentration, catalyst loading, pH, temperature, and airflow rate. Under optimal conditions (200 mg L-1 dye, 4 g L-1 TiO2, pH 6, 40 degrees C, 0.2 L min-1 airflow), 94 % of AOG and 81.37 % of total organic carbon were removed within 105 min. The photodegradation followed first-order kinetics, and the Arrhenius equation was applied to determine the temperature dependence. Internal mass transfer limitations were assessed through calculations of the effective diffusion coefficient, Thiele modulus, and effectiveness factors, indicating that the reaction rate was mainly controlled by the chemical step. These findings demonstrate the process's potential for synthetic wastewater treatment and offer practical insights for improving dye removal strategies in environmental applications.
Keywords: Astrazon Orange G; Photocatalysis; TiO2; Kinetics; Intraparticle diffusion effects; Response surface methodology